2018
DOI: 10.1063/1.5010346
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ion implantation enabled bio-functionalization of PEEK improves osteoblastic activity

Abstract: Slow appositional growth of bone in vivo is a major problem associated with polyether ether ketone (PEEK) based orthopaedic implants. Early stage promotion of osteoblast activity, particularly bone nodule formation, would help to improve contact between PEEK implantable materials and the surrounding bone tissue. To improve interactions with bone cells, we explored here the use of plasma immersion ion implantation (PIII) treatment of PEEK to covalently immobilize biomolecules to the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Functionalizing cell-interfacing surfaces with cell-modulatory proteins can also improve the biological properties of the implant. For example, the ECM protein tropoelastin has been shown to promote the biological behavior of human osteoblast-like osteosarcoma cells (SAOS-2) on PEEK via plasma immersion ion implantation (PIII) treatment (Wakelin et al, 2018 ). Adiponectin (APN), which is adipocyte-secreted adipokine, has been confirmed to increase the osteogenic ability in vitro and osseointegration in vivo of sPEEK implants (Wang et al, 2019 ; Deng et al, 2020 ).…”
Section: Modifications Inspired By the Components Of Bonementioning
confidence: 99%
“…Functionalizing cell-interfacing surfaces with cell-modulatory proteins can also improve the biological properties of the implant. For example, the ECM protein tropoelastin has been shown to promote the biological behavior of human osteoblast-like osteosarcoma cells (SAOS-2) on PEEK via plasma immersion ion implantation (PIII) treatment (Wakelin et al, 2018 ). Adiponectin (APN), which is adipocyte-secreted adipokine, has been confirmed to increase the osteogenic ability in vitro and osseointegration in vivo of sPEEK implants (Wang et al, 2019 ; Deng et al, 2020 ).…”
Section: Modifications Inspired By the Components Of Bonementioning
confidence: 99%
“…[14] Some of the performance deficits may arise from the relatively low surface energy of PEEK that makes it more hydrophobic than titanium, other metals and other polymers. [17] A range of modifications of PEEK has been examined, including wet chemistry, plasma treatments, coating or blending with biomaterials known for their osteoconductive properties, such as titanium and hydroxyapatite. [13,18] Plasma immersion ion implantation (PIII) is a form of plasma treatment that imparts significantly more energy to the ions bombarding the surface than conventional plasma treatments and implants them at depth in the treated material.…”
Section: Introductionmentioning
confidence: 99%
“…PIII can modify the flat surface of commercially available PEEK sheets to promote bone cell adhesion and spread. [17] It has been shown that the high energy of ion bombardment available in PIII allows covalent binding to take place when an initially adsorbed molecule reacts with a radical diffusing to the surface, as shown for tropoelastin to PEEK. [17,21] Covalency of protein binding to PIII-treated PEEK has been demonstrated by the resistance to attempted removal of the bound protein with a detergent solution containing 5% sodium dodecyl sulphate at 80°C for 10 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, polymer materials are divided into universal polymer (such as polypropylene and polymethyl methacrylate), engineering polymer (such as polyamide 66 and polyformaldehyde), and special polymer (such as polyetheretherketone and polytetrafluoroethylene [PTFE]). Polypropylene, polymethyl methacrylate, polyamide 66, polyformaldehyde, polyetheretherketone, and PTFE all have brilliant tribological performances for applications. Hence, the polymer bearing balls might be suitable for tribological applications due to their excellent tribological nature.…”
Section: Introductionmentioning
confidence: 99%